Economic Cycle Policy — Post COVID-19 - Überblick (Wirtschaftsdienst)
Abstract The coronavirus crisis has plunged the German economy into the deepest recession since the Second World War. Due to its global spread, supply chains have been disrupted and international trade has been severely impaired, which has hit the export-dependent German economy particularly hard. The economic stimulus package of the German government is criticized by the authors in many points. Some assess above all the temporary reduction of the value added tax as too general to provide an economic stimulus. They claim that companies suffer most from the pandemic and are the main driving force of potential growth. They propose an improvement in the tax treatment of losses and a reduction in income taxes. Others focus on public investment as a driver of growth and call for future investments for an innovative, digital and climate-neutral economy.